Kondisi Ekonomi, Dan Kesehatan Pemulung Di Tempat Pembuangan Akhir Gampong Jawa - Fitri, Rahma; Sakdiah, Sakdiah; Zulyadi, Teuku Zulyadi (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2024)
The existence of a final disposal site (TPA) in Gampong Jawa makes it one of the places for people to earn a living. Many people outside Banda Aceh come to Gampong Jawa to settle and work as scavengers so that it is known as a slum. The purpose of this study is to find out the conditions of scavengers with the community in Gampong Jawa and to find out the economic conditions of the scavenger community as seen from the conditions of income, expenditure and health. The method used in this study is a qualitative method with a sampling technique, namely purposive sumption. The data collection techniques used are observation, interviews and documentation. The results obtained in this study are that the economic conditions of the scavenger community are below the average UMR income, which is 50,000 or even less per day. The expenses of each scavenger differ depending on the number of dependents in the family, some are sufficient and some must be sufficient, where there is no savings, so this condition causes them to be vulnerable to their welfare.